Correction to: Fucosidosis in Tunisian patients: mutational analysis and homology-based modeling of FUCA1 enzyme - Latifa Chkioua; Yessine Amri; Sahli Chaima; Ferdawes Fenni; Hela Boudabous; Hadhami Ben Turkia; Taieb Messaoud; Neji Tebib; Sandrine Laradi (BMC, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.